2003
DOI: 10.1007/s10123-003-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability of bacterial populations in tropical soil upon exposure to Lindane

Abstract: The effect of the pesticide Lindane on microbial populations was analyzed in soil with a history of contamination with various chemicals, including this pesticide. Soil microcosms were amended with 100 mg Lindane/kg soil and microbial populations were monitored for 70 days. Bacterial cell concentrations, metabolic versatility (whole community Biolog), and genetic diversity (16S rDNA/denaturing gradient gel electrophoresis) were used to monitor microbial communities. Results show the persistence of Lindane in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Feidieker et al (1994) reported reduced microbial diversity in soil containing HCHs (up to 11,055 mg kg )1 ) and other chlorinated aromatic compounds (up to 18,500 mg kg )1 CB and 132 mg kg )1 CP), using selective culture techniques, metabolic testing on microtitre plates and fatty acid analyses. In a 70-day study, Rodriguez & Toranzos (2003) used Biolog, 16S rDNA and denaturing gradient gel electrophoresis (DGGE) analyses to monitor the diversity of bacteria in a tropical soil with a history of HCH contamination and spiked with 100 mg kg )1 c-HCH. Within two weeks, overall bacterial cell numbers were reduced by 50% relative to the non-spiked control.…”
Section: Hch Concentrationmentioning
confidence: 99%
“…Feidieker et al (1994) reported reduced microbial diversity in soil containing HCHs (up to 11,055 mg kg )1 ) and other chlorinated aromatic compounds (up to 18,500 mg kg )1 CB and 132 mg kg )1 CP), using selective culture techniques, metabolic testing on microtitre plates and fatty acid analyses. In a 70-day study, Rodriguez & Toranzos (2003) used Biolog, 16S rDNA and denaturing gradient gel electrophoresis (DGGE) analyses to monitor the diversity of bacteria in a tropical soil with a history of HCH contamination and spiked with 100 mg kg )1 c-HCH. Within two weeks, overall bacterial cell numbers were reduced by 50% relative to the non-spiked control.…”
Section: Hch Concentrationmentioning
confidence: 99%
“…1, which revealed the microbial metabolic activity in the aged oil sludge (Rodriguez and Toranzos, 2003). Logistic model was applied to fit the data points according to Nakatani et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…The growth and activity of denitrifying bacteria was adversely affected by lindane (Sáez et al, 2006). A reduction of 50% in bacterial cell concentration was observed in lindane-amended soil microcosms (Rodríguez and Toranzos, 2003). HCH also reduces plant seed germination and seedling viguor (Bidlan et al, 2004).…”
Section: Lindane In the Environmentmentioning
confidence: 96%